THE EFFECT OF USING PSYLLIUM SEED (Plantago ovata) POWDER IN BROILER DIETS ON SOME QUALITATIVE CHARACTERISTICS OF THE CARCASS AND CHEMICAL CHARACTERISTICS OF MEAT: THE EFFECT OF USING PSYLLIUM SEED (Plantago ovata) POWDER IN BROILER DIETS ON SOME QUALITATIVE CHARACTERISTICS OF THE CARCASS AND CHEMICAL CHARACTERISTICS OF MEAT (Iraqi Journal of Market Research and Consumer Protection, 2026)
This experiment was conducted in the poultry field of the Poultry Research Station / Department of Livestock Research / Office of Agricultural Research for the period from January 13 to February 23, 2023. In this experiment, 300 one-day-old Ross308 chicks were used, with an average weight of 38.1 g. The chicks were distributed randomly upon the chambers at 10 birds for each replicant and in five treatments, and Plantago ovata seed were used in the diets at 0, 0.4, 0.6, 0.8 and 1% for each of the T1, T2, T3, T4 and T5. No significant differences were observed between the treatments for both the dressing percentage and the relative weights of the liver, heart, gizzard and neck. It also showed a high significant increase (P≤0.01) in the relative weight of the chest in treatments T3 and T4 compared to treatment T2. Treatments T2, T4 and T5 recorded a high significant increase (P≤0.01) in the relative weight of the thigh piece compared to the control treatment and the treatment T3. It is noted that there was a high significant increase (P≤0.01) in the relative weight of the drum stick for each of the treatments T1, T2 and T5 compared to the treatments T3, T4. The results showed a high significant decrease (P≤0.01) in fat oxidation indicators (malondialdehyde, peroxide value, free fatty acids) in all treatments of the experiment compared to the control treatment during the first period of meat storage. A high significant decrease (P≤0.01) in the concentration of total volatile nitrogen in treatments T4, T5 compared to the control treatment. A high significant increase (P≤0.01) in water holding capability of treatments T3, T4 and T5 compared to the control treatment. A high significant decrease (P≤0.01) in fat oxidation indicators (malondialdehyde, peroxide value, free fatty acids) in T3, T4, T5 compared to the control treatment in the second period of storage. A high significant decrease (P≤0.01) in the concentration of total volatile nitrogen in treatments T3, T4 and T5 compared to the control treatment. As for water holding capability of meat, the results showed a high significant increase (P≤0.01) in treatments T3, T4 and T5 compared to the control treatment. We conclude from this study that using Psyllium seed powder in diets by 0.4-1% may improve the physiological and immune-tissue characteristics of broilers.